Comparison of the Effect of Nd:YAG and Diode Lasers and Photodynamic Therapy on Microleakage of Class V Composite Resin Restorations - Siavash Savadi Oskoee (Journal of Dental Research, Dental Clinics, Dental Prospects, 2013)
Background and aims. Considering the importance of disinfecting dentin after cavity preparation and the possible effect of disinfection methods on induction of various reactions between the tooth structure and the adhesive restorative material, the aim of the present study was to evaluate microleakage of composite resin restorations after disinfecting the prepared dentin surface with Nd:YAG and Diode lasers and photodynamic therapy. Materials and methods. Standard Class V cavities were prepared on buccal surfaces of 96 sound bovine teeth. The samples were randomly divided into 4 groups based on the disinfection method: Group 1: Nd:YAG laser; Group 2: Diode laser; Group 3: photodynamic therapy; and Group 4: the control. Self-etch bonding agent (Clearfil SE Bond) was applied and all the cavities were restored with composite resin (Z100). After thermocycling and immersing in 0.5% basic fuchsin, the samples were prepared for microleakage evaluation under a stereomicroscope. Data was analyzed with Kruskal-Wallis and Wilcoxon signed-rank tests at P<0.05. Results. There were no significant differences in the microleakage of occlusal and gingival margins between the study groups (P>0.05). There were no significant differences in microleakage between the occlusal and gingival margins in the Nd:YAG laser group (P>0.05). In the other groups, microleakage at gingival margins was significantly higher than that at the occlusal margins (P<0.05). Conclusion. Nd:YAG and Diode lasers and photodynamic therapy can be used to disinfect cavity preparations before composite resin restorations.